Les Baumettes au musée : Graffitis et créations carcérales - Jean-Fabien Philippy (Criminocorpus)
The planned demolition of the historic buildings of the Baumettes prison in 2018 has prompted the “musée des civilisations de l’Europe et de la Méditerranée”, the Museum of Europe and Mediterranean civilisations (Mucem) to launch the "Graffitis et créations carcérales", "Graffiti and prison creation" investigation in early 2019. Taking up the question of prisons and confinement, the survey has two parts: on the one hand, the compilation of photographic documentation in partnership with the “Inventaire général du patrimoine culturel PACA”, PACA region’s General inventory of heritage, which takes as its subject the prison as such (its buildings and architecture, its graffiti) and, on the other, a collection of items displayed in the cells, objects created by the inmates and relating to their daily life.The survey took the form of more than two thousand photographs taken by the “Inventaire général du patrimoine culturel PACA”, PACA region’s General inventory of heritage, one hundred and forty documents collected in the cells and corridors, and forty-two items listed in the museum's inventory, either from cells left abandoned when prisoners were transferred to the new Baumettes 2 site, or from items seized by the prison administration.